Judicialização da saúde e sustentabilidade de gastos: o caso dos medicamentos para o Estado do Ceará - Rodrigues, Henrique Rosa (2011)
The judicialization of Health in Brazil has been increasing significantly in the past few years, bringing also a series of obstacles to the Brazilian National Health System- Sistema Único de Saúde (SUS) – as the public power is asked for disbursing recourses for the attendance of the requested proceedings against the states. It is in this context, that the Coordination of Pharmaceutical Assistance of the State of Ceará - Coordenadoria de Assistência Farmacêutica do Estado do Ceará (COASF) – specifically, in its exceptional component, translates itself into the most required sector by these instruments in face of the peculiarities and complexities inherent to itself, such as the gradual insertion of new medicines in the marketplace, great variability of people who prescribe and, mainly, the unaccomplished guidelines contained in the Clinical Protocols and Therapeutic Guidelines - Protocolos Clínicos e Diretrizes Terapêuticas (PCDT) - of SUS. The judicialization has been an instrument for the access of the medications for some, but it can also compromise the rationality of the public management when it imposes unplanned expenses by the system which may generate opportunity costs and the dismantle of the public budget. This dissertation has as a main goal the analysis of the expenses of the interventions of the process of the judicialization of medications managed by the COASF of the Health Secretariat of Ceará State - Secretaria da Saúde do Estado do Ceará (SESACE). With the usage of econometric instruments, we could describe the behavior of expenses with the demands for medications requested in a administratively and / or judiciary way (GMAJ). The study, performed by the augmented Dickey-Fuller (ADF) unit root test, demonstrated that the series of GMJA has an explosive behavior, that is, it presents unit roots, demonstrating that these demands are growing indefinitely, as time goes by, and that, per hour, haven’t yet taken the series of total expenses (GTM) of SESA/COASF to have a similar behavior to the presented by the GMJA. The tendency of this process is that the GTM could be compromised, since the result of the GMJA demonstrates an explosive behavior, this, however, doesn’t unbalance the budget and the public finances.